2002
DOI: 10.1038/sj.mp.4001121
|View full text |Cite
|
Sign up to set email alerts
|

D2S2944 identifies a likely susceptibility locus for recurrent, early-onset, major depression in women

Abstract: Recurrent, early-onset, major depressive disorder (RE-MDD) is a strongly familial condition whose malignant effects have a significant negative impact on the health and longevity of patients and their family members. Sixteen of the 19 candidate susceptibility loci identified by a recent genome survey revealed allelic associations with RE-MDD in men or women, but not in both sexes. The association of D2S2944 alleles and genotypes with RE-MDD and related disorders was evaluated using a case-control study design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
30
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 47 publications
5
30
0
Order By: Relevance
“…Work by Zubenko and colleagues has also suggested a role of CREB1 on mood disorders; this lies 20 cM centromeric to our linkage peak (Zubenko et al, 2003a). These authors have also identified a sex-specific association between the 124bp repeat allele of D2S944 and recurrent, early-onset major depression and with anxious depression in an independent U.S. and Dutch sample (Beem et al, 2006;Philibert et al, 2003;Zubenko et al, 2002). Due to the high level of comorbidity between alcohol and drug dependence and major depression, and as indexed by a high LOD score of 3.49 for comorbid alcoholism and major depression in prior linkage analyses using COGA data (Nurnberger, Jr. et al, 2001), this region on chromosome 2 may be tapping into a region of susceptibility for both disorders.…”
Section: Discussionsupporting
confidence: 58%
“…Work by Zubenko and colleagues has also suggested a role of CREB1 on mood disorders; this lies 20 cM centromeric to our linkage peak (Zubenko et al, 2003a). These authors have also identified a sex-specific association between the 124bp repeat allele of D2S944 and recurrent, early-onset major depression and with anxious depression in an independent U.S. and Dutch sample (Beem et al, 2006;Philibert et al, 2003;Zubenko et al, 2002). Due to the high level of comorbidity between alcohol and drug dependence and major depression, and as indexed by a high LOD score of 3.49 for comorbid alcoholism and major depression in prior linkage analyses using COGA data (Nurnberger, Jr. et al, 2001), this region on chromosome 2 may be tapping into a region of susceptibility for both disorders.…”
Section: Discussionsupporting
confidence: 58%
“…Hence, its reported effects on recurrent early-onset MDD in females (Zubenko et al, 2002b) do not seem to generalize to these quantitative risk factors.…”
Section: Discussionmentioning
confidence: 98%
“…Those effects occur in the absence of evidence for linkage, although the association cannot be spurious due to stratification effects because the association is partitioned in between and within family contributions. Zubenko et al (2002b) reported association for recurrent early-onset MDD in females only. Although we did not find any association for females, some evidence for linkage in this region was found for anxious depression as judged by the estimates of the variances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, individuals with more than one episode of depression may also have earlier ages at onset, more severe episodes, more comorbid disorders, and a stronger family history of psychopathology. It is also conceivable that all of these clinical picture variables reflect an underlying genetic vulnerability to the recurrent type of depression, particularly given the likely genetic transmission of recurrent depression (Kendler et al, 1992;Sullivan et al, 2000;Zubenko et al, 2002). Earlier age at onset, more severe early episodes of depression, greater comorbidity, and greater family history of psychopathology may all reflect an underlying genetic predisposition to the more severe recurrent type of depression.…”
mentioning
confidence: 99%